Left Gastric Artery Variants: A Cadaveric, Postmortem and Radiological Investigation - Ande, Thanuja; Makani, Thanuja Kumari; Nannam, Kavya; Velichety, Subhadra Devi; Jyothi, Ashok Kumar (Scripta Medica, 2023)
Background/Aim: Anatomical variations of the gastric vessels during laparoscopic surgeries of the stomach and related viscera frequently impair the surgeon's judgment, extend the duration of surgery and sometimes can lead to accidental surgical injuries, rendering it not possible to assure the safety and effectiveness of the surgical treatment. This research paper aimed to examine the variations of the left gastric artery (LGA), which could have implications for surgical and interventional procedures of the gastrointestinal tract (GIT) and related organs.Methods: Fifty specimens, of which 22 were dissected from cadavers and 28 were acquired from post-mortems among the Indian population, regardless of age or sex were examined for variant LGA. In addition, the variation of the celiac trunk was observed in 10 patients using 3D-CT images, which were created by reconstructing multiple-slice computed tomography (CT) using 3-dimensional CT simulation software (3D-CT). Results: The classical pattern origin of LGA from the celiac trunk was observed in 96 % specimens. In 2 % gastrophrenic trunk emerged from the abdominal aorta (AA) slightly proximal to the celiac trunk, then it branched into LGA and left and right inferior phrenic arteries. In remaining 2 %, LGA was the branch of the splenic artery. In 10 individuals radiological examination was conducted and found no abnormal pattern of celiac trunk.Conclusion: Observing and reporting the variation in the gastric vessels by different methods has certain clinical value in upper gastrointestinal surgeries and interventions. The duration can be prolonged and the intraoperative blood loss is increased with the vascular variations. Overall, this research paper provides important information on the prevalence of anatomical variations of the LGA, which could help improve the safety and efficacy of upper gastrointestinal procedures.